THE RELATIONSHIP BETWEEN STRESS LEVELS AND SLEEP QUALITY WITH THE MENSTRUAL CYCLE ON NURSING STUDENTS - Ernawati, Dianna Ika; Ekawati, Heny; Gumelar, Wahyu Retno; Rahmadani, Alvi (Journal of Vocational Nursing, 2024)
Introduction: Every month's regular menstrual cycle should ideally span 21-35 days.  The menstrual cycle is influenced by several factors, namely stress levels and sleep quality. Menstrual cycle disorders indicate metabolic and endocrine system irregularities. The impact that often occurs due to menstrual cycle disorders is infertility and difficulty identifying the fertile period. The purpose of the study was to determine the relationship between stress levels and sleep quality with the menstrual cycle in seventh-semester nursing students at Universitas Muhammadiyah Lamongan. Methods: This research design uses correlation analytics with a cross-sectional approach using a simple random sampling technique with a sample of 111 respondents. Measured using the Depression Anxiety Stress Scale questionnaire sheet for stress levels and the Pittsburgh Sleep Quality Index questionnaire for sleep quality. After tabulating the data and analyzing it using the Spearmen Rank test. Results: This study showed that almost half of the 43 female students (38.7%) experienced mild stress and more than half of the 60 female students (54.1%) had poor sleep quality.  Conclusions: Based on the results of the analysis using the Spearmen rank test, the value of p = 0.000, where p <0.05 means that there is a relationship between stress levels and sleep quality with the menstrual cycle in nursing students in semester VII of Universitas Muhammadiyah Lamongan. Based on this research, it is expected that female students can reduce stress, get enough sleep 7-8 hours, diet, and control weight so that the menstrual cycle returns to normal.